Plasticizers: Negative impacts on the thyroid hormone system - BEREKETOĞLU, CEYHUN (My University, 2022)
This review aims to understand the impacts of plasticizers on the thyroid system of animals and humans. The thyroid gland is one of the earliest endocrine glands that appear during embryogenesis. The thyroid gland synthesizes thyroid hormones (TH), triiodothyronine (T3), and thyroxine (T4) that are important in the regulation of body homeostasis. TH plays critical roles in regulating different physiological functions, including metabolism, cell growth, circadian rhythm, and nervous system development. Alteration in thyroid function can lead to different medical problems. In recent years, thyroid-related medical problems have increased and this could be due to rising environmental pollutants. Plasticizers are one such group of a pollutant that impacts thyroid function. Plasticizers are man-made chemicals used in a wide range of products, such as children\"s toys, food packaging items, building materials, medical devices, cosmetics, and ink. The increased use of plasticizers has resulted in their detection in the environment, animals, and humans. Studies indicated that plasticizers could alter thyroid function in both animals and humans at different levels. Several studies demonstrated a positive and/or negative correlation between plasticizers and serum T4 and T3 levels. Plasticizers could also change the expression of various TH-related genes and proteins, including thyroid-stimulating hormone (TSH), thyrotropin-releasing hormone (TRH), and transporters. Histological analyses demonstrated thyroid follicular cell hypertrophy and hyperplasia in response to several plasticizers. In conclusion, plasticizers could disrupt TH homeostasis and the mechanisms of toxicity could be diverse.
Keywords: Tarımsal Bilimler; Çevre Mühendisliği; Mühendislik ve Teknoloji; Agricultural Sciences; Environmental Engineering; Engineering and Technology; ÇEVRE BİLİMLERİ; Çevre / Ekoloji; Tarım ve Çevre Bilimleri (AGE); ENVIRONMENTAL SCIENCES; ENVIRONMENT/ECOLOGY; Agriculture & Environment Sciences (AGE); Aquatic Science; Nature and Landscape Conservation; Environmental Science (miscellaneous); Physical Sciences; Life Sciences; Thyroid; Thyroid hormones; Phthalates; Environmental pollutants; Metabolism; NON-PHTHALATE PLASTICIZERS; SOLID-PHASE EXTRACTION; N-BUTYL PHTHALATE; DI(2-ETHYLHEXYL) PHTHALATE; BISPHENOL-A; DIISONONYL PHTHALATE; DIETHYL PHTHALATE; URINARY PHTHALATE; ACID ESTERS; DI-(2-ETHYLHEXYL) PHTHALATE; Thyroid; Thyroid hormones; Phthalates; Environmental pollutants; Metabolism